Mitochondrial Dysfunction, Genetic Predisposition, and Targeted Interventions in Neurodegenerative Diseases and Cognitive Decline: A Meta-Analysis of Mechanisms and Treatments - Bano, Sher; Lohana, Sonam; Gottimukkala, Harsha Sai Krishna; Saad, Saja; Saad, Mohammed; Maloth, Arun Kumar; Uzair, Muhammad; Al Shamsi, Meera; Mohamed, Ahmed Elawady (Indus Journal of Bioscience Research, 2025)
Background: Neurodegenerative diseases (NDs) and cognitive decline pose a growing global health burden. Mitochondrial dysfunction and genetic predisposition are key contributors to disease progression. This meta-analysis evaluates their impact on cognitive decline and mitochondrial function while assessing potential therapeutic interventions. Methods: A systematic search was conducted across PubMed, Web of Science, PsycINFO, Cochrane Library, and Scopus (2015–2024). Eligible studies included RCTs, case-control, and experimental research examining mitochondrial dysfunction (ATP, ROS, MMP, mitophagy markers, DNA stability) and genetic factors (APOE4, PINK1, PARK2, TFAM) in Alzheimer’s, Parkinson’s, ALS, Huntington’s, and multiple system atrophy. A random-effects model (Hedges’ g) was used to calculate effect sizes. Results: Nine studies (n = 2,560) showed a significant association between mitochondrial dysfunction and cognitive decline (Hedges’ g = 0.85, 95% CI: 0.60–1.10, p = 0.003). APOE4 had the strongest correlation (OR = 2.10, 95% CI: 1.70–2.50, p < 0.001). Mitochondrial-targeted therapies improved cognitive function and mitochondrial stability. UDCA enhanced ATP synthesis (12% improvement, p = 0.02), liraglutide reduced oxidative stress (8%, p = 0.04), and TFAM gene therapy improved mitochondrial DNA repair (14%, p = 0.01). Moderate heterogeneity (I² = 42%) and minor publication bias were observed. Conclusions: This meta-analysis underscores the pivotal role of mitochondrial dysfunction and genetic predisposition in neurodegenerative disease progression. The findings highlight the potential of mitochondrial-targeted therapies in slowing cognitive decline, offering promising avenues for clinical intervention. Despite some heterogeneity, the consistency of effect sizes reinforces the reliability of these results. Future research should prioritize large-scale, standardized trials with long-term follow-up, incorporating novel biomarkers and precision medicine approaches to enhance clinical applicability and improve treatment strategies for neurodegenerative disorders.